2015
DOI: 10.5713/ajas.15.0308
|View full text |Cite
|
Sign up to set email alerts
|

Models for Estimating Genetic Parameters of Milk Production Traits Using Random Regression Models in Korean Holstein Cattle

Abstract: The objectives of the study were to estimate genetic parameters for milk production traits of Holstein cattle using random regression models (RRMs), and to compare the goodness of fit of various RRMs with homogeneous and heterogeneous residual variances. A total of 126,980 test-day milk production records of the first parity Holstein cows between 2007 and 2014 from the Dairy Cattle Improvement Center of National Agricultural Cooperative Federation in South Korea were used. These records included milk yield (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
5
5
0
1
Order By: Relevance
“…Decreasing reproductive performance after approximately 5 parities can be explained by an increase in twinning rate and conception rate with age (Fourie & Heydenrych, 1983). The results from this study were in agreement with those reported by Baneh, Hafezian, Rashidi, Gholizadeh, and Rahimi (2009). As reported by Ekiz et al (2005), effect of ewe age on reproductive traits of different sheep breeds is common.…”
Section: Genetic Trendsupporting
confidence: 93%
“…Decreasing reproductive performance after approximately 5 parities can be explained by an increase in twinning rate and conception rate with age (Fourie & Heydenrych, 1983). The results from this study were in agreement with those reported by Baneh, Hafezian, Rashidi, Gholizadeh, and Rahimi (2009). As reported by Ekiz et al (2005), effect of ewe age on reproductive traits of different sheep breeds is common.…”
Section: Genetic Trendsupporting
confidence: 93%
“…The mean daily milk yield during the early lactation for the 2 nd party is higher by 2.32 litters (13.4%) than the daily mean milk yield for the 1 st parity. This agreed with Cho et al (2016) who reported a difference between first and second parity as for stage of lactation. The pattern of mean daily milk production throughout the lactation period (Fig 1) and during the early lactation stage (Fig 2) indicated that first lactation cows have the lowest peak yields but the highest days in milk (DIM) at peak and more persistent than the second lactation cows.…”
Section: Lactation Stage and Lactation Curvesupporting
confidence: 90%
“…The higher total and daily milk yield in the second parity cows during the early lactation is since mature cows can gain body weight and condition quickly after calving whereas the first calvers face lactation stress and partition nutrients for continuous body growth and milk production which is in agreement to Kashoma et al (2015). Also, this shows the same result that persistency of lactation in the first parity is higher than in the second parity but there was a lower peak milk yield in the first parity (Cho et al 2016). However, higher daily milk yield in the first parity cows obtained during the late lactation (fig 3)might be related to the ability to gain body weight and condition in the first calvers at a late stage after full recovery from lactation stress and full mature age.…”
Section: Lactation Stage and Lactation Curvesupporting
confidence: 73%
“…Kaps and Spehar (2004) obtained higher heritability for fat yield for 305 days 0.31 and lower heritability 0.27 for protein yield for Simmental cattle than in our study. Cho et al (2016) reported low test-day heritability estimates ranged from 0.08 to 0.15 for milk, 0.06 to 0.14 for fat, 0.08 to 0.12 for protein according to days in milk in Holstein breed cows. Kheirabadi and Razmkabir (2016) observed low heritability estimates for milk 0.204, fat 0.096 and protein 0.047 to Holstein cattle.…”
Section: Resultsmentioning
confidence: 98%